UPAYA ADAPTASI MASYARAKAT DI DAERAH RAWAN BENCANA KEBAKARAN HUTAN DAN LAHAN DI DESA SUNGAI TOHOR KECAMATAN TEBING TINGGI TIMUR KABUPATEN KEPULAUAN MERANTI - Zatul, Pais; Jalil, Ashaluddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Infrastructure development activities in 2007 have resulted in dry peat. Two years later PT. LUM built canals up to 7 meters deep and about 5 meters wide, making the peat drier. The prolonged effect of these activities caused the community to lack water and there was a great fire in 2014 which caused many losses. Although restoration has been carried out, it has not eliminated traces of vulnerability to fire. So that the purpose of this study is to see the adaptation efforts made by the community in minimizing the occurrence of land fires in the future. The author interviewed 6 informants with a descriptive qualitative approach and was determined based on purposive. The results showed that community adaptation has been running well, where structurally the government has been able to answer and fulfill the physical infrastructure for wetting the peat. On the economic side, the community is getting used to it and has many alternative livelihoods without managing land using fire. They no longer use the method to clear land because it is considered to have the potential to cause fires. The weak point is the lack of economic strengthening so that people do not fully believe that they can survive without managing peatlands in the usual way.Â Keywords: Adaptation, Forest and Land Fires, Tohor River